Implementasi Dan Manfaat Ice Breaking Dalam Meningkatkan Minat Dan Hasil Belajar Peserta Didik SDN Blok I Cilegon - Maulia Rahmawati; Patra Aghtiar Rakhman; Siti Rokmanah (Universitas Sarjanawiyata Tamansiswa, 2023)
There are still many teachers who conduct learning that is not fun or seems monotonous, causing a lack of interest in learning from students. So, this needs to be done Ice Breaking to break the atmosphere of the class. Good implementation of ice breaking in the learning process in the classroom can improve students' learning concentration ability, ability to absorb, learning interest, learning attention, and learning outcomes, and can improve student achievement. By implementing ice-breaking in learning, it is hoped that students will be able to learn in a pleasant and comfortable atmosphere. This research uses a descriptive qualitative approach with triangulation techniques. The validity of the interview material was tested through observation techniques and an in-depth examination of activities related to the research material. The researcher then analyzed the material at the data reduction stage, presented the data, and then drew conclusions. The results of this study are the benefits of implementing ice breaking at SDN Blok I Cilegon, which has a very good impact because it will be able to restore conditions, and the class will be more conducive for students to concentrate on the teacher delivering the subject matter. Although the ice breaking used is only light physical movement activities by moving the limbs, such as yells, clapping together, singing or cheering songs. The implementation of ice-breaking can also affect the learning outcomes of students.